Kandungan Timbal pada Kulit, Daging, dan Insang Ikan Juaro (Pangasius polyuranodon) di Sungai Musi Palembang - Emilia, Ita; Eddy, Syaiful; Saputra, Ari Yansyah (Jurnal Dosen Universitas PGRI Palembang)
AbstractHas conducted research titled Metal Content of Lead (Pb) in Part Leather, Meat and Fish Gills Juaro (Pangasius polyuranodon) in the waters of the River Musi Palembang, which was conducted in April-June 2014 This study aims to determine the concentration of lead metal (Pb ) on the skin, meat and fish gills Juaro waters of the Musi River in Palembang. The method used is descriptive quantitative research methods. The sample used is composed of the skin, meat and fish gills Juaro. The results showed that the metal concentrations of lead (Pb) in some parts of the fish Juaro are as follows: the average concentration of lead (Pb) in the skin of 0.897 mg / kg, in the meat section at 1,700 mg / kg, and the average lead (Pb) in the gills of 2,526 mg / kg. At the gills have exceeded the quality standards set by the Food and Drug Administration (FDA) is> 2.0 mg / kg.Keywords: Lead, Fish Juaro, Musi River